2016
DOI: 10.1371/journal.pone.0160677
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Subgroups of Small-for-Gestational-Age: Differential Neurodevelopmental Outcomes

Abstract: ObjectivesIt remains unclear why substantial variations in neurodevelopmental outcomes exist within small-for-gestational-age (SGA) children. We prospectively compared 5-y neurodevelopmental outcomes across SGA etiological subgroups.MethodsChildren born SGA (N = 1050) from U.S. Early Childhood Longitudinal Study-Birth Cohort (2001–2007) was divided into etiological subgroups by each of 7 well-established prenatal risk factors. We fit linear regression models to compare 5-y reading, math, gross motor and fine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additionally, the smaller twins are growth restricted and consequently small for gestational age (SGA). Children born SGA often suffer from impaired brain development likely resulting in long-term cognitive or motor disabilities [20,21,22]. Hence, being born SGA also negatively affects the neurodevelopmental status of the smaller twin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the smaller twins are growth restricted and consequently small for gestational age (SGA). Children born SGA often suffer from impaired brain development likely resulting in long-term cognitive or motor disabilities [20,21,22]. Hence, being born SGA also negatively affects the neurodevelopmental status of the smaller twin.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not conduct a mediation analysis to disentangle the direct effect of TSE on neurodevelopment from its indirect effect on preterm birth/low birth weight. Further, prior research indicates that term infants who were exposed to in-utero TSE and who were small for gestational age born have lower reading and math scores at age 5 compared to unexposed children 48 . Other studies on term infants reported lower Bayley scores in areas such as Motor, Cognition, Language, and Adaptive Behavior at age 2 11 , 12 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Due to sample size limitations, we did not conduct separate analyses for term and preterm-born children and for SGA children born to mothers with or without a hypertensive disorder of pregnancy, or those who smoked during pregnancy, as prior studies suggested that there are variations in neurodevelopmental outcomes within SGA children. 29 However, we corrected for GA at delivery in our multivariable analysis. Although the association between SGA and lower odds of low IQ score in children persisted despite adjusting for multiple covariates, we acknowledge the possibility of unmeasured residual confounding.…”
Section: Discussionmentioning
confidence: 99%